2003
DOI: 10.5414/cnp59341
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure in the tropics: emerging trends from a tertiary care hospital in South India

Abstract: Sepsis continues to be the predominant cause of ARF. Overall mortality of our patients is better, because of the case mix, a large percentage of patients had acute gastroenteritis as a cause of CRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…The overall mortality rate (22%) was lower than previously reported in developed and emerging countries (2,16,24), and the mortality rate in patients receiving RRT (32.3%) was much lower than in BEST (60.3%) and PICARD (45.3%) (2,44). These results are probably related to higher mean APACHE scores in PICARD (86 versus 56 in our study) (16).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The overall mortality rate (22%) was lower than previously reported in developed and emerging countries (2,16,24), and the mortality rate in patients receiving RRT (32.3%) was much lower than in BEST (60.3%) and PICARD (45.3%) (2,44). These results are probably related to higher mean APACHE scores in PICARD (86 versus 56 in our study) (16).…”
Section: Discussioncontrasting
confidence: 55%
“…Studies from developing countries have shown that AKI incidence varies (14,(19)(20)(21)(22)(23) and that AKI is often community acquired and preventable (i.e., due to gastroenteritis and infections) (23)(24)(25)(26)(27). However, a formal comparison between developed and emerging countries is lacking (14,28).…”
Section: Introductionmentioning
confidence: 99%
“…[2728293031] Severe diarrhea and PSGN form a large proportion of children with AKI in India. [3233] In our study, acute glomerulonephritis (predominantly PSGN) accounted for 7.6% of patients. Diarrhea leading to AKI was uncommonly encountered.…”
Section: Discussionmentioning
confidence: 63%
“…However, sub-Saharan African (SSA) countries face the dual burden of non-communicable and transmissible diseases which may predispose to an increase in prevalence and a modified spectrum of kidney diseases [ 8 ]. Despite epidemiological transition in this setting, CKD remains the leading kidney disease, affecting predominantly young male adults, in their economically productive years, with chronic glomerulonephritis, hypertension and diabetes as the main etiological factors [ 9 – 16 ] while AKI is mainly secondary to diarrhea, obstetric complications, toxins and infections [ 17 , 18 ]. Few countries in SSA have nephrologists and where available, nephrology units are under-equipped and understaffed; hence, patients with kidney diseases are generally managed in general internal medicine wards [ 11 ].…”
Section: Introductionmentioning
confidence: 99%